Conversion to resection of liver metastases from colorectal cancer with hepatic artery infusion of combined chemotherapy and systemic cetuximab in multicenter trial OPTILIV. - Lévi, FA (2017)
BACKGROUND: Systemic chemotherapy typically converts previously unresectable liver metastases (LM) from colorectal cancer to curative intent resection in ∼15% of patients. This European multicenter phase II trial tested whether hepatic artery infusion (HAI) with triplet chemotherapy and systemic cetuximab could increase this rate to 30% in previously treated patients. PATIENTS AND METHODS: Participants had unresectable LM from wt KRAS colorectal cancer. Main non-inclusion criteria were advanced extra hepatic disease, prior HAI and grade 3 neuropathy. Irinotecan (180 mg/m(2)), oxaliplatin (85 mg/m(2)) and 5-fluorouracil (2800 mg/m(2)) were delivered via an implanted HAI access port and combined with i.v. cetuximab (500 mg/m(2)) every 14 days. Multidisciplinary decisions to resect LM were taken after every three courses. The rate of macroscopic complete resections (R0 + R1) of LM, progression-free survival (PFS) and overall survival (OS) were computed according to intent to treat. RESULTS: The patient population consisted of 42 men and 22 women, aged 33-76 years, with a median of 10 LM involving a median of six segments. Up to 3 extrahepatic lesions of <1 cm were found in 41% of the patients. A median of six courses was delivered. The primary end point was met, with R0-R1 hepatectomy for 19 of the 64 previously treated patients, 29.7% (95% confidence interval 18.5-40.9). Grade 3-4 neutropenia (42.6%), abdominal pain (26.2%), fatigue (18%) and diarrhea (16.4%) were frequent. Objective response rate was 40.6% (28.6-52.3). Median PFS and OS reached 9.3 (7.8-10.9) and 25.5 months (18.8-32.1) respectively. Those with R0-R1 hepatectomy had a median OS of 35.2 months (32.6-37.8), with 37.4% (23.6-51.2) alive at 4 years. CONCLUSION: The coordination of liver-specific intensive chemotherapy and surgery had a high curative intent potential that deserves upfront randomized testing.